Analisis Catch Per Unit Effort (CPUE) dan Maximum Sustainable Yield (MSY) Ikan Kembung Lelaki (Rastrelliger kanagurta) yang Didaratkan Di Pelabuhan Perikanan Samudera (PPS) Kendari - ahmadhusni muzahid S; Utama Kurnia Pangerang; Andi Irwan Nur (Universitas Mataram, 2024)
The Banda Sea is an Indonesian water body that holds potential for small pelagic fisheries resources. Situated between Sulawesi Island and Maluku, it is part of the Fisheries Management Area Of The Republic Of Indonesia (WPP-NRI 714), Male mackerel (Rastrelliger kanagurta) is one of the fish species with high economic value, greatly favored by the community for consumption. This has led to an increase in its capture rates. Therefore, the research aims to determine the CPUE and MSY of Indian mackerel in the Kendari Ocean Fisheries Port. Data collection was conducted at the Kendari Ocean Fisheries Port from logbooks, and the research lasted from November to December 2023. The results showed that the standard fishing gear used to catch these fish is purse seine. The status of the utilization of the fishery resources is said to be experiencing underfishing. Based on the research results, the maximum sustainable yield (MSY) is 96,386 kg/year, with an optimal fishing effort of 2,300 trips/year (Fox model).